POLYOXYETHYLENE POLYOXYPROPYLENE BLOCK COPOLYMERS - A NOVEL PHASE-TRANSITION IN AQUEOUS-SOLUTIONS OF PLURONIC-F87 (POLOXAMER-237) - Mitchard, N; Beezer, A; Rees, N; Mitchell, J; Leharne, S; Chowdhry, B; Buckton, G (1990)
An unexpected phase transition in dilute aqueous solution of the nonionic surfactant poloxamer P237 (Pluronic F87), with an excess specific heat capacity maximum at 307.7 K in the concentration range 1-10 mg/ml, has been observed using high sensitivity differential scanning calorimetry (HSDSC); the thermodynamic parameters associated with this transition are reported.